Trends in cognitive function before and after myocardial infarction: findings from the China Health and Retirement Longitudinal Study - Shang, Jing; Dong, Jianye; Zhu, Sijia; Chen, Qingmei; Hua, Jianian (Frontiers in Aging Neuroscience, 2024)
Objectives: Incident stroke was associated with cognitive dysfunction after stroke and even before stroke. However, cognitive trends prior to myocardial infarction (MI) and the timeline of cognitive decline in a few years following incident MI remain unclear, especially among the Chinese population. We aimed to evaluate whether MI was associated with cognitive change both before and after MI in China. Methods: This cohort study included 11,287 participants without baseline heart problems or stroke from the China Health and Retirement Longitudinal Study. The exposure was self-reported MI. The outcomes were scores of cognitive functions in five domains, which reflected abilities of episodic memory, visuospatial abilities, orientation, attention and calculation, and global cognition as a summary measure. A Linear mixed model was constructed to explore cognitive function before and after incident MI among the MI participants and the cognitive trends of participants free of MI. Results: During the 7-year follow-up, 421 individuals (3.7% of 11,287, mean [SD] age, 60.0 [9.0] years; 59.1% female) experienced MI events. The cognitive scores of participants of both the MI group and the control group without MI declined gradually as time went by. The annual decline rate of the MI group before incident MI was similar to that of the control group during the whole follow-up period. Incident MI was not associated with acute cognitive decline in all five cognitive domains. Moreover, MI did not accelerate the cognitive decline rate after MI compared with the pre-MI cognitive trends. The decline rate of cognitive function after MI was similar to the rate before MI. Conclusions: Different from stroke, participants who had an MI did not show steeper cognitive decline before MI. MI was not associated with acute cognitive decline and accelerated decline in several years after MI. Future studies are needed to learn the mechanisms behind the different patterns of cognitive decline between MI and stroke.